Global orders and civilizations: Perspective from history, philosoophy and international relations - (:unkn) unknown (Nova Science Publishers, Inc., 2009)
The explosion of new themes and working areas in social sciences in the aftermath of the Cold-War stimulated the 'cultural turn' of the previous decades and strengthened the position of the notion of 'civilization' as a unit of analysis and locus of academic debate in the fields of history, philosophy, sociology, political science, and international relations. Given the fabricated and standardized nature of recent literature on political, economic and socio-cultural aspects of globalization, it is crystal clear that historically and philosophically enlightened works written from the perspective of civilizational transformation will provide the much needed sophistication to conventional social science analyses trying to elucidate the organizing principles of the global order. This novel collection represents a path-breaking work in the field of global/civilizational studies by constituting an interdisciplinary and theoretically-informed platform on which complex debates on the political, economic, socio-cultural, philosophical and ecological aspects of the global order could be conducted. The editors, Sadik Ünay and Muzaffer Şenel, managed to gather a truly original collection of articles from some of the leading authorities and promising academics on the theme of global orders with special reference to a civilization transformation covering a wide spectrum in time and space from Antique Greece to the Islamic World, from Europe to the US and from East Asian history to current globalizations. Contributions rooted in the disciplines of history, philosophy, sociology, anthropology, political science and global political economy are craftsmanly combined to give the reader a holistic vision towards the possibility of multiple civilizational experiments and global orders. This book which boldly endeavours to transcend narrow boundaries of conventional academic approaches and Western-centric prejudices in various branches of social sciences will be a must-read for students of globalization, cultural studies and macro-history. © 2009 by Nova Science Publishers, Inc. All rights reserved.